COMPARATIVE STUDY OF EFFECTS AND ADVERSE REACTIONS OF LEVOCETIRIZINE, RUPATADINE AND MOMETASONE IN PATIENTS OF ALLERGIC RHINITIS - Reddy, Rukma; I, Sridhar; B, Srikanth (International Journal of Clinical and Biomedical Research, 2018)
Aim: To compare the therapeutic efficacy and safety of Rupatadine and mometasone with Levocetirizine which is most commonly used drug. To study the effects of levocetirizine, Rupatadine and mometasone on absolute eosinophil count and IgE levels. Methodology: The participants were randomly divided into 3 groups of 25 patients each and treated as follows: Group I: were treated with Levocetirizine 5mg OD for 14 days, Group II: were treated with Rupatadine 10mg OD for 14 days, Group III: were treated with Mometasone two sprays (50mcg of mometasone in each spray) in each nostril once daily (total daily dose of 200mcg) for 14 days. The patients were asked to report at the hospital after 14 day and they were followed up with regard to clinical improvement of symptoms and signs and any adverse effects as reported by the patient. Rhinoscopy finding, X- ray of para nasal sinus, improvement in symptoms (sneezing, Itching, nasal discharge, nasal blockage and anosmia) Absolute eosinophils count, Serum IgE levels and adverse reports were studied and investigation were compared before and after treatment. Result: Rhinoscope finding showed treatment with mometasone became normal but X- Ray of para nasal sinus results showed levocetirzine showed higher rate of improvement. In improvement of symptoms sneezing, itching and nasal discharge was high mometasone. In all groups post treatment there was no changes in Ig E and Absolute Eosinophils count. ADR reported with mometaxone. Conclusion: The three drugs, levocetirizine, rupatadine and mometasone were found to have similar levels of efficacy in controlling the symptoms of the allergic rhinitis. The physical signs improved better with mometasone than the other 2 drugs. The 3 drugs levocetirizine, rupatadine and mometasone had no significant effect on the absolute eosinophil count and the serum IgE levels. Adverse effects were found to be more with levocetirizine than the other two drugs. Considering this factor and also the fact that long term use of corticosteroids like mometasone is undesirable, rupatadine appears to be a better choice in the treatment of allergic rhinitis.